2003
DOI: 10.1073/pnas.1237797100
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Zn superoxide dismutase mutants associated with amyotrophic lateral sclerosis show enhanced formation of aggregates in vitro

Abstract: Mutations in Cu͞Zn superoxide dismutase (SOD) are associated with the fatal neurodegenerative disorder amyotrophic lateral sclerosis (ALS). There is considerable evidence that mutant SOD has a gain of toxic function; however, the mechanism of this toxicity is not known. We report here that purified SOD forms aggregates in vitro under destabilizing solution conditions by a process involving a transition from small amorphous species to fibrils. The assembly process and the tinctorial and structural properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
273
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(295 citation statements)
references
References 38 publications
(50 reference statements)
20
273
1
1
Order By: Relevance
“…This conclusion emphasizes the observed correlation between the effects of mutations and the onset of diseases (12,17,23,26). It is a reassuring result in the context of studies of this type that the physicochemical principles observed through experiments involving simplified noncellular environments are so relevant to the systems in vivo.…”
Section: Evaluation Of the Stabilities And Aggregation Propensities Omentioning
confidence: 60%
“…This conclusion emphasizes the observed correlation between the effects of mutations and the onset of diseases (12,17,23,26). It is a reassuring result in the context of studies of this type that the physicochemical principles observed through experiments involving simplified noncellular environments are so relevant to the systems in vivo.…”
Section: Evaluation Of the Stabilities And Aggregation Propensities Omentioning
confidence: 60%
“…For most experiments herein, we employed a well-established pseudo WT (pWT) construct in order to facilitate measurements of stability and aggregation of reduced apo SOD1s and avoid complications caused by aberrant disulfide bond formation (8,(14)(15)(16)(20)(21)(22). In pWT, the nonconserved free cysteines at residues 6 and 111 are replaced by alanine and serine, respectively, whereas the highly conserved cysteines at residues 57 and 146 are retained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1A). Numerous in vivo and in vitro studies have shown that various immature, destabilized forms of SOD1 are prone to aggregate, and this is often enhanced by disease-associated mutations (8)(9)(10)(11)(12)(13)(14)(15)(16). Recently, attention has focused on aggregation of the most immature form of SOD1, in which the disulfide bond is reduced and no metals are bound (reduced apo).…”
mentioning
confidence: 99%
“…Overexpression of SOD1 mutants in rodents recapitulates ALS clinical and pathological hallmarks through a toxic gain of function (1). Many mutations in SOD1 decrease its stability and increase its unfolding rates and propensity to aggregate (2). High molecular weight complexes of SOD1 are observed in mammalian cells and spinal cords of transgenic mice expressing this mutant protein (3).…”
Section: Neurodegeneration ͉ Protein Misfoldingmentioning
confidence: 99%